The Lives of Muhammad: By Kecia Ali (Cambridge, MA: Harvard University Press, 2014. 342 pages.) (American Journal of Islam and Society, 2016)
The title of Kecia Ali’s latest book, The Lives of Muhammad, suggests thatit is another biography of the Prophet. And it very much is that book, not asbiography but as historiography, cultural study, and the methods of the Studyof Religion. By focusing narrowly on the material, she is able to be expansivein her thought and raise several important issues in the study of Muhammad’slife, both from the perspective of the believer and the non-believer.Most importantly, and what makes this book particularly successful, is thatshe recognizes conflict and contradiction without offering resolution. Theresult is a work that can be extremely useful in classroom settings, in additionto making a valuable contribution to what we think about the meaningsof Muhammad.The work is structured into six chapters, with shorter introduction andconclusion sections. However, the length of these two sections belies the depthof material contained therein. In the introduction, Ali maps out the scope ofher project: a diachronic study of the biographies of Muhammad. She arguesfor the increasing dialogic between non-Muslim and Muslim views of theProphet, especially since the nineteenth century. Her statement of what shechose to exclude is greatly appreciated, for it helps point out that there is a greatdiversity of Muslim thought concerning Muhammad. By making the breadthof the material omitted explicit, she allows the reader to understand in moreconcrete terms her statement that “[religious] traditions have always been internallyheterogeneous” (p. 3).The first chapter focuses on questions of constructing a historical Muhammad.Ali begins with a basic outline of the Muslim narrative version of hislife story, but immediately begins to bring up some of the issues, both in termsof the sources and the narrative’s neatness. She explicitly mentions Hagarismand the more recent work of Fred Donner in laying out the historical contextof Muhammad. She then deftly works through this scholarship, giving the ...